DESIGN OF A VALIDATED HPTLC METHODOLOGY FOR THE MEASUREMENT OF LINOLEIC AND OLEANOLIC ACID IN ECLIPTA ALBA (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Eclipta alba (Asteraceae Family) is a widely recognised medicinal plant found in tropical and subtropical regions of the world. It is one of the plants that is most frequently utilised in traditional medical systems including Ayurveda, Sidha, homoeopathic, Unani, Chinese, and folk medicine. Many significant phytochemical components, including triterpenes, flavonoids, coumestans, steroids, saponins and polypeptides, are present in each portion of this medicinal plant. Several herbal and Ayurvedic formulations, like Indulekha Bringha oil and Liv.52 Gnx pill, contain Eclipta alba as a important therapeutic ingredient. The objective of the current work was to create a validated and consistent HPTLC technique for the simultaneous measurement of linoleic acid (LA) and oleanolic acid (OA) in E. alba. The procedure used Silica Gel 60 F254 as the stationary phase and ethyl acetate, toluene, and formic acid at a ratio of (4:7:0.2 v/v/v) as the mobile phase, which produced compact bands upon derivatization with anisaldehyde sulfuric acid. The correlation coefficient (r2) for the linear regression data for the standard linoleic and oleanolic acid calibration curves was 0.9966 and 0.9964, respectively, and it demonstrated a good linear relation over range of concentrations of 300-1500 ng/spot and 450-1600 ng/spot with respect to the area. Precision, accuracy, robustness, and selectivity of the approach were all assessed. LOD and LOQ for LA and OA, respectively, were measured to be 108.47 and 182.33 ng/spot and 258.30 and 327.54 ng/spot. We came to the conclusion that this approach, which uses HPTLC to quantify LA and OA, is effective, straightforward, accurate, and reproducible.